Analisis Pengaruh Pemberian Cangkang Kemiri Terhadap Nilai Parameter Batubara di CV. Bara Mitra Kencana, Sawahlunto - Ilal Fajri Setiawan; Heri Prabowo (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. CV. Bara Mitra Kencana is a mining company engaged in coal mining, located in the city of Sawahlunto, West Sumatra. Coal produced by CV. Bara Mitra Kencana Consists of various types, which are grouped based on their calorific value originating from different pits. These coal calories are influenced by the geological conditions of a mining location, including high quality, medium quality and low quality coal. With differences in coal quality at each coal seam, the coal mixing process is necessary. done so that low quality coal can be utilized. Research with this method aims to determine the effect of low quality coal when mixed with hazelnut shells, the use of a mixture of candlenut shells on coal will see its effect on calories, sulfur, ash, total moisture, fixed carbon and coal volatile matter.Based on the results of the above research shows where the initial coal calorie is 4700 cal / g to 6443.11 cal / g, the initial coal sulfur is 2.66% to 0.079%, the initial coal moisture inherent is 1.91% to 4.39%, Volatile The initial coal matter was 27.54% to 31.88%, the initial coal Ash content was 30.17% to 14.45%, the initial coal fixed carbon was 40.38% to 50.18%. Keywords : coal quality, candlenut shells, calories, ash content, sulfur, volatile matter